Pengaruh Jarak Sumber Jet Terhadap Temperatur Dinding Selinder - Kaprawi (Universitas Sriwijaya, 2009)
Free jet flow coming out from a rectangulaire orifice has temperature higher than than the ambient. This flow attack a cilynder so the wall temperature of cilynder will increase. The results show that the small temperature gradient at cilynder wall occur when the cilynder is palced far from the orifice. Near the orifice or jet source so great temperature gradient occur at the front wall of the cilynder. While at the back wall, starting from the separasion region, the temperature gradient is not high. The wider of orifice cross section the smaller temperature of waal cilynder.